Development-dependent scavenging of nucleic acids in the filamentous fungus Aspergillus fumigatus. - Jöchl, C; Loh, E; Ploner, A; Haas, H; Hüttenhofer, A (2009)
Aspergillus fumigatus is an ubiquitous, filamentous and opportunistic pathogenic fungus which causes fatal invasive aspergillosis among immuno-compromised patients. Since therapeutic strategies are currently limited, the mortality rate of invasive aspergillosis is high and thus, alternative antifungal strategies are required. In this study, we demonstrate that during vegetative growth Aspergillus fumigatus is able to scavenge nucleic acids within its cell wall with accumulation rates of several thousand-fold, compared to the surrounding medium. To investigate, whether nucleic acids, attached to the fungal cell wall, are able to move further into the cytoplasm of fungal cells, we directly applied siRNAs, in the absence of lipo-transfection reagents, to growing A. fumigatus cells. In fact, addition of two 21-nt siRNA duplexes resulted in knock-down of their corresponding target mRNAs, odcA and pyrG, respectively. These findings indicate that RNA interference, mediated by siRNAs, can be used as a fast and efficient tool to investigate the functions of genes within filamentous fungi. In addition, siRNA-based therapies may provide novel approaches for antifungal treatment.